A Critical Reading of Social Consciousness in K. V. Raghupathi’s Orphan and other Poems - Sunitha, V.; Gopalkrishna, Nagakala Nanjangud; Sameera, Asma (International Journal of Psychosocial Rehabilitation, 2020)
Dr. Raghupathi is one of the leading voices in Indian English Poetry. Although by nature a mystic poet, three of his individual collections written and published over a decade are replete with themes dealing with various social realities. Through his poems the prudent poet enlightens and creates social awareness. The bard’s elegant and vibrant verses instill tenacity and resilience in the minds of readers. He is a Pollyanna and enlightens us with the ray of sunshine. The present paper is an earnest endeavor to unearth the above mentioned virtues in the select poems of his tenth poetry collection Orphan and other Poems